Arbuscular mycorrhizal fungi associated with tangerine (Citrus reticulata) in Chiang Mai province, northern Thailand, and their effects on the host plant - Youpensuk S. (2014)
There are many tangerine (Citrus reticulata) orchards in northern Thailand. These orchards are supplied with different levels of fertilizers. The objective of this study is to investigate arbuscular mycorrhizal (AM) fungi associated with tangerine in Chiang Mai province, northern Thailand, and the effect of AM fungi on the growth of the air layered tangerine variety 'Sai Num Phung' with different levels of nitrogen (N) and phosphorus (P) fertilizers in a pot experiment. Percentage of AM colonization in the tangerine roots and spore density in the rhizosphere varied significantly with the available P levels in the orchard soil. Means of root colonization and spore density were significantly depressed at >500 mg P/kg soil. Twenty-two species of AM fungi were found to be associated with tangerine in orchards of the Chiang Mai province. The effects of AM fungi, and N and P fertilizers on air layered tangerine plants were investigated in pots for ten months. AM fungi increased growth of the host plant especially in pots with N but without P fertilizers. AM fungi increased concentrations of P and Mg in leaves of tangerine. Application of N and P fertilizers depressed root colonization of AM fungi in the pot experiment. This study has shown that a wide range of AM fungi is associated with tangerine in commercial orchards, but with high levels of N and P fertilizers the increase in growth of tangerine trees due to the association with AM fungi may be limited.